The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/su10072478
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study on the Design of China High-Speed Rail Express Train Operation Plan—From a Sustainable Transport Perspective

Abstract: Abstract:The sustained and steady development of China's economy has led to the rapid improvement of the logistics. At the same time, the rise of the e-commerce mode has given rise to a huge demand for express delivery and the express industry has entered a period of boom. Fortunately, China's high-speed rail network has been networked, and the development of a high-speed rail express train has entered the test stage. After the high-speed rail express train is put into use, it could effectively relieve the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…With the continuous expansion of the high-speed railway (HSR) in China [1], the formulation of passenger ticket strategies has attracted more attention. The single pricing policy of the HSR is facing flexible and diverse price competition from other modes of transportation, which leads to unbalanced capacity utilization with fluctuations in passenger flow.…”
Section: Introductionmentioning
confidence: 99%
“…With the continuous expansion of the high-speed railway (HSR) in China [1], the formulation of passenger ticket strategies has attracted more attention. The single pricing policy of the HSR is facing flexible and diverse price competition from other modes of transportation, which leads to unbalanced capacity utilization with fluctuations in passenger flow.…”
Section: Introductionmentioning
confidence: 99%
“…China, the country with the largest HSR network, has developed new types of freight train for speeds of 250-350 km/h. Yu et al [2] reported on the design of a two-stage model for the HSR cargo express operation which meets the needs of technical and economical requirements of train operation. The first-stage model considers the line capacity, loading restrictions and origin-destination demand.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Railway traffic constitutes a significant part of travels, which is considered as a safe, efficient and comfortable transportation. Nowadays, rail transport is also one of important choice for passengers all over the world [1]. It is well known that potential safety hazards resulting from material/structural degradation under the cyclical loading and natural erosion.…”
Section: Introductionmentioning
confidence: 99%